Pathological self-criticism : assessment and treatment - Bergner, Raymond M. (Plenum series in social/clinical psychology., 1995)
Raymond M. Bergner offers the first comprehensive reference to address the highly prevalent and debilitating forms of self-criticism. This resource features an extensive array of strategies for assessing these patterns as well as the factors maintaining them. In addition, the volume is complete with therapeutic intervention strategies to help patients abandon pathological self-critical practices. The author desribes a therapeutic relationship that greatly enchances the efficacy of the interventions mentioned throughout the book.